Aspirin-clopidogrel combination therapy for ischemic stroke patients: Clinical efficacy and cost-effectiveness analyses in low-resource setting - Fitria, Najmiatul; Febiana, Dian; Akram, Muhammad; Yosmar, Rahmi (Narra J, 2024)
Understanding the cost-effectiveness of aspirin-clopidogrel combination therapy is crucial in determining its influence on coagulation parameters, specifically prothrombin time (PT) and activated partial thromboplastin time (APTT). The aim of this study was to assess the cost-effectiveness and clinical impact of using the aspirin-clopidogrel combination compared to aspirin alone in managing ischemic stroke. Employing an observational research design, inpatient ischemic stroke cases receiving the aspirin-clopidogrel combination were compared to those treated with aspirin alone. Focusing on the hospital's perspective on costs, the research specifically analyzed medical expenses without discounting costs or effects. The analysis involved comparing the direct medical costs and coagulation parameters between the two treatment groups. Our data revealed that the aspirin-clopidogrel combination demonstrated superior cost-effectiveness over aspirin alone, indicated by the incremental cost-effectiveness ratio (ICER) values for PT (IDR -246,930/second) and APTT (IDR -119,270/second). This indicated that the combination therapy was associated with lower costs while yielding better clinical parameter values. The ICER analysis placed the aspirin-clopidogrel combination in the southeast quadrant, marking its dominance over aspirin monotherapy by demonstrating higher effectiveness at lower costs. These results suggest that combination therapy might be a favorable alternative for managing ischemic stroke, presenting a viable option for consideration in clinical practice. The findings underscore the potential economic and clinical advantages of employing the aspirin-clopidogrel combination in routine stroke management protocols.